Delayed Treatment and Missed Opportunities for Limb Salvage in Patients with Peripheral Arterial Embolism - Nasto, Lefter; Kavrakov, Tanyo (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: The peripheral arterial embolism (PAE) is a sudden decrease in limb perfusion due to acute occlusion of peripheral artery which leads to ischemic tissue damage, that can threaten the limb of a patient and requires immediate revascularization. It is estimated that the incidence of acute limb emoblism in the general population is around 14/100,000 inhabitants per year. Accurate and timely diagnosis is crucial to salvage the patient’s limb and sometimes the patient’s life. In cases of complete arterial occlusion and absence of collateral perfusion, irreversible damage can occur within 4 to 6 hours. The fundamental definition for treatment of acute peripheral arterial embolism is revascularisation. Revascularisation is either performed endovascularly or by an open surgical approach. A suspicion of acute ischemia based on history and physical examination warrants heparin administration and vascular surgery consultation. Delays in the management of acute peripheral arterial ischemia due to an embolism are common and associated with poor limb - salvage outcomes. AIM: Our study aims to identify medical consultations and cardiovascular assessments undergone by patients in the period prior to being hospitalised, in order to evaluate for missed or delayed opportunities for diagnosis. METHODS: Retrospective cohort study, utilising the medical documentation and previous outpatiently or inhospital consultations. Adult patients undergone treatment due to peripheral arterial embolism were identified and analyzed. Patients were identified through the administrative hospital database using the International Classification of Diseases. Hospitalised patients with those medcodes between 1st January 2010 - 1st March 2020 were recorded. RESULTS: Following exclusion, 424 patients (mean age 68.5 ± 5.85 years) were included. 159 patients (66.8%) had visited their family doctors or other medical specialist before admission and in all of the cases was initiated therapeutic approach. The rest of the cohort 79 patients (33.2%) presented lately due to other social reasons. The group of 159 patients that admitted lately due to medical indications - diagnostic, healthcare - administrative or treatment related problems are subject of our study. The largest group including 113 (71%) patients were treated outpatientley by vascular surgeons with preventative medications.17 patients (10.6%) were directed outpatientley to orthopaedic surgeon due to suspicion of trauma.15 patients (9.4%) were treated by their family doctors with pain relief medications. The rest of the 14 patients (8.8%) were treated by neurosurgeons or neurologists due to a suspicion of cauda eniqua and other neuropathies. The majority of the patients 108 (67.9%) were free of complains at the discharge, 11.3% of the studied cohort were with minimal post-treatment complains (numbness, coldness, absent peripheral pulsations, insignificant claudicatio). Amputation rate was 14.4%, incidence of rethrombosis 8.8% and recurrent embolism frequency around 3.7%. Death was registered in 21 cases (13.2%). CONCLUSION: The consequences of acute limb embolism such as prolonged hospitalization, major limb amputation, and/or death have a profound socioeconomic impact. Unrecognition of this vascular pathology and differential diagnosis difficulties are possibly leading factors for delayed or missed treatment.